2020
DOI: 10.1177/1369433220950610
|View full text |Cite
|
Sign up to set email alerts
|

The impact of uneven temperature distribution on stability of concrete structures using data analysis and numerical approach

Abstract: Temperature variation is an essential factor to influence the stability of concrete structure. In contrast to the uniform distribution of temperature in most existing approaches, this paper aims to study the natural temperature distribution in concrete structure and analyze its impact on structural mechanical behaviors in field. As a case study, an underwater shield tunnel is investigated using the presented method. Firstly, temperature sensors are installed in different positions to achieve real-time monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In recent years, researchers have chosen to introduce support vector machine methods and design program experiments to optimize the temperature-monitoring techniques in various fields such as oil and gas pipelines, rail transportation, and bridge construction [16,17]. Confronted with the challenges of temperature monitoring in structural engineering, existing research has utilized data analyses and numerical methods to establish multiple linear regression models for optimization [18,19]. In the field of temperature monitoring for oil and gas pipelines, how to use optimization methods to improve the temperature-monitoring performance of the BOTDA system has always been a research hotspot, domestically and internationally.…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, researchers have chosen to introduce support vector machine methods and design program experiments to optimize the temperature-monitoring techniques in various fields such as oil and gas pipelines, rail transportation, and bridge construction [16,17]. Confronted with the challenges of temperature monitoring in structural engineering, existing research has utilized data analyses and numerical methods to establish multiple linear regression models for optimization [18,19]. In the field of temperature monitoring for oil and gas pipelines, how to use optimization methods to improve the temperature-monitoring performance of the BOTDA system has always been a research hotspot, domestically and internationally.…”
Section: Related Workmentioning
confidence: 99%
“…It was suggested that the change of concrete Young’s modulus with temperature was the primary reason for the variations in modal characteristics. Tan et al (2021) and Zhang et al (2021) argued that the non-uniform temperature gradient mode can affect the mechanical properties of the structure to a significant extent. In terms of nonlinear models, Ding and Li (2011) determined the relationship between modal frequency and temperature by using the six-order polynomial regression model based on the long-term monitoring data of Runyang suspension bridge located in China.…”
Section: Introductionmentioning
confidence: 99%
“…These conventional heat-transfer analysis adopts a divide-and-conquer strategy. That is, the main components, such as the deck and towers, are modeled separately as 2D FE models by disregarding the temperature variation along the longitudinal direction (Zhou et al, 2016; Xia et al, 2019; Tan et al, 2021) or local 3D FE models (FEMs) (Xia et al, 2013, 2020; Zhu and Meng, 2017). These local models are analyzed individually to obtain the temperature distribution of the cross sections, which are then assembled manually and input into the global 3D FEM of the bridge for the structural analysis to calculate temperature-induced responses (Xia et al, 2013; Zhu and Meng, 2017).…”
Section: Introductionmentioning
confidence: 99%